'Characters reall': Francis Bacon, China and the entanglements of curiosity. Issue 2 (11th February 2014) - Lux, Jonathan E.
<x xml:space="preserve">Abstract</x> This article explores Francis Bacon's numerous references to China, Chinese people and Chinese technologies in the context of the projected impression of China available to early modern England. Bacon knew a great deal about China and, rather than simple flights of fancy or empty rhetorical gestures, his descriptions of China were serious claims in keeping with orthodox intelligence on the subject. These claims have significant implications in the context of contemporary criticism on Bacon's philosophy of language and his reading of Chinese 'Characters reall'. Furthermore, the hazy spectre of China that emerges from the collection of those scattered references provides a clear precedent for the scientocratic, utopian vision prefigured in the New Atlantis and central to Bacon's philosophical programme as a whole.